2018
DOI: 10.3390/ma11091652
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in Curie Temperature of Yttrium Iron Garnet by Doping with Neodymium

Abstract: The effect of the substitution of Y3+ by Nd3+ on the structural and magnetic properties of neodymium-doped yttrium iron garnet, NdxY3−xFe5O12 with x in the range of 0–2.5, is presented. Oxide powders of Fe2O3, Nd2O3, and Y2O3 were mixed in a stoichiometric ratio and milled for 5 h using high-energy ball milling, before being uniaxially pressed at 900 MPa and annealed at 1373 K for 2 h to obtain NdxY3−xFe5O12 (0 ≤ x ≤ 2.5). It was found that the mechanical milling of oxides followed by annealing promotes the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…33 Figure 4 shows the changes of T C during heating and cooling and are marked with black dashed lines; T C decreases by roughly 10 K with increasing content of Er from x = 0 to 0.20. Considering a reported T C of YIG at around 560 K, 34 the T C of the Er:YIG slightly decreases by substituting Er into YIG.…”
Section: Resultsmentioning
confidence: 99%
“…33 Figure 4 shows the changes of T C during heating and cooling and are marked with black dashed lines; T C decreases by roughly 10 K with increasing content of Er from x = 0 to 0.20. Considering a reported T C of YIG at around 560 K, 34 the T C of the Er:YIG slightly decreases by substituting Er into YIG.…”
Section: Resultsmentioning
confidence: 99%
“…López et al observed an increasing trend of lattice parameter in the study of neodymium-substituted YIG. [21] Figure 3 shows the SEM patterns of all the Y 2 GdFe 5 O 12 samples sintered at different temperatures. From the patterns, it can be clearly seen that the grain growth increases and the porosity decreases with the sintering temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Strong [65] Moderate [68] Strong [69] Permeability High [70] Moderate [71] Moderate [30] Magnetic Loss Low [72] Low [71] Low [30] Frequency Range…”
Section: Yig Gdig Dyig Saturation Magnetizationmentioning
confidence: 99%